Triple band fractal koch antenna for wearable application - A. Rahim, Mohamad Kamal (2012)
This report presents Triple-band Fractal Koch Textile antenna using first iteration of Koch geometry of a dipole antenna structure for wearable applications. In order to reduce the overall length of the dipole antenna structure, the flare angle of the antenna design is varied to three different values which are 30, 45 and 60 degree respectively. The radiating elements of the antenna are made of adhesive copper fabric, whilst the substrate is given a property of denim textile material. The proposed antennas are simulated in CST Studio and have been optimized to operate within the ISM frequency bands (0.902–0.928 GHz, 2.4–2.5 GHz and 5.725–5.875 GHz). The simulation results are then compared with valid measurements and the results are further discussed in this paper.